The ombudsman revisited: thirty years of Hawaiian experience - Hill, Larry B. (2002)
This article examines the classical, or real, ombudsman. Unlike quasi ombudsmen, which are bureaucratic control mechanisms subject to executive leaders or agency administrators, real ombudsmen are operationally independent officials of the legislative branch. In 1969, the state of Hawaii was the first to create a real ombudsman. Although lowa, Nebraska, Alaska, and Arizona have since followed Hawaii's lead, no intensive, long-term study of American ombudsmen has yet been published. This article examines the ombudsman as a monitor of Hawaii's bureaucracies and considers the extent to which the office has become institutionalized over the past 30 years. Nearly 75,000 citizens have had their complaints investigated by the ombudsman, and more than one-fifth of them were rectified, that is, the agency reversed its original action. This study indicates that the classical ombudsman can become institutionalized in the United States. The findings have policy implications as jurisdictions at the federal, state, and local levels consider the creation of ombudsmen or quasi ombudsmen. - Reproduced.
Keywords: Ombudsman